The distance learning impact on the quality of the educational process (according to the study results conducted at the State University of Management) - I. K. Shcherbakova (Цифровая социология)
Digitalization is gaining momentum at a rapid pace, affecting all spheres of society, including education, where, as a result of the global Covid-19 pandemic, a forced transition from full-time to distance learning, digital format was carried out. However, the quality of educational activities during this transition has significantly decreased, as evidenced by numerous studies in 2020-2023. Therefore, it is necessary to comprehend the main problems associated with the reduction of traditional classroom educational practices and the transition from offline learning format to online format.   The study purpose is to clarify the students’ opinion about the quality of educational activities in the distance learning format; to identify difficulties encountered by participants in the educational process in connection with the emergency transition to online learning; to determine the prospects of the developed online learning system at the higher education level.   To achieve this goal, theoretical and empirical research methods were used, as well as qualitative and quantitative analysis of the data obtained. The sample consisted of the responses of 100 1st-year students of the State University of Management who receive professional education in various fields of training. As a result of processing the students’ responses, a generally positive attitude towards distance education was noted, however, forced digitalization revealed the negative sides of this transition. In this regard, it is proposed to form recommendations on the need to develop the principles of an educational process combined system, providing for a combination of online and offline formats. In addition, the author’s task is to offer modern interactive techniques that will be used on online platforms in order to increase interest in learning and improve the quality of the educational process.